Comparison of Surgeon Expectations to Patient-Reported Outcomes Following Open Carpal Tunnel Release - Melissa E. Cullom; John P. Hajj; Shahnur Ahmed; Erin L. Weber; Ryan J. Kozlowski; Khusboo J. Desai; Anthony J. Archual; Brian M. Christie (HAND, 2026)
Background: Open carpal tunnel release (OCTR) is an effective surgical treatment option for carpal tunnel syndrome (CTS). This study evaluates hand surgeon expectations of postoperative recovery versus patient-reported outcomes following OCTR through Patient-Reported Outcomes Measurement Information System (PROMIS) surveys. Methods: Patients who underwent OCTR (Common Procedure Terminology 64721) for CTS performed by 5 hand surgeons were evaluated (2021-2024). PROMIS pain-interference (P-PI) and pain-upper extremity (P-UE) surveys were completed at 2-week, 6-week, and 3-month intervals postoperatively. Patients who underwent simultaneous hand procedures with OCTR and/or had perioperative complications were excluded. Hand surgeons completed PROMIS P-PI and P-UE surveys for theoretical patient groups to predict postoperative recovery in the same timeframe. Higher P-PI scores suggest greater pain, and higher P-UE scores suggest better functionality. Results: Sixty-eight patients were included. Among patients with minimal comorbidities/mild CTS (n = 33), surgeons predicted less pain (P-PI = 38.7 vs 54.8, P = .004) and better functionality (P-UE = 59.8 vs 35.5, P = .00005) compared to mean patient scores at 3 months postoperatively. For patients with multiple comorbidities/mild CTS (n = 17), surgeons predicted less pain (P-PI = 40.7 vs 52.7, P = .013) and better function (P-UE = 53.0 vs 41.3, P = .034) at 3 months postoperatively. In the same cohort, surgeons predicted better function at 2 weeks postoperatively (P-UE = 30.4 vs 36.2, P = .032). For severe CTS patients (n = 18), surgeons predicted less pain (P-PI = 45.6 vs 54.3, P = .009) and better function (P-UE = 37.9 vs 28.5, P = .047) at 6 weeks postoperatively. Conclusions: Hand surgeons may be overly optimistic about recovery timelines for patients undergoing OCTR, specifically underestimating how pain may interfere with daily tasks and their upper-extremity function at 3 months postoperatively.